On the Approximation of Stochastic Concurrent Constraint Programming by Master Equation - Bortolussi, Luca (Electronic notes in theoretical computer science, 2008)
We explore the relation between the stochastic semantic associated to stochastic Concurrent Constrain Programming (sCCP) and its fluid-flow approximation. Writing the master equation for a sCCP model, we can show that the fluid flow equation is a first-order approximation of the true equation for the average. Moreover, we introduce a second-order correction and first-order equations for the variance and the covariance.